Understanding the Experiences of Survivors of a Loss by Suicide: A Photovoice Study. Issue 1 (2nd January 2019) - Mayton, Heather Nicole; Wester, Kelly
ABSTRACT: Suicide is a devastating loss that leaves behind many survivors who are left to cope with unique obstacles such as isolation, stigma, and the question of why the death occurred. All of these aspects can lead to negative mental health consequences and make it difficult to express the grief experience verbally. Words may not provide the fullest description of the experience, but photographs may provide survivors the opportunity to share their experience on a deeper level. In this study, the researchers used photovoice methodology to explore the experience of survivors. The result included seven themes with a total of 15 photos. These enriching photographs not only give voice to survivors of suicide, but also bring the survivors' voices out of isolation and provide other individuals within the survivors' community with a powerful message of their grief experiences.